Strategi Awal Pengembangan Usaha Omichli Vapor Sebagai Toko Vape Rintisan Di Bekasi - Raden Ahmad Syailendra; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Omichli Vapor is a start-up business that focuses on selling vape products and accessories in Bekasi City. This study aims to formulate an initial strategy for business development by referring to qualitative and secondary primary data analysis. The methods used in this study include observations of early customers, interviews, and literature and market data studies. The results of the analysis show that Omichli Vapor's main strength lies in friendly service and unique local liquid variations, at affordable prices. Based on these findings, this study recommends strengthening digital channels and community approaches as short-term strategies for business development.